Aramay's sinnon a Ga'dang weaving story - Balansi, Margareth; Salvador-Amores, Analyn V. (University of the Philippines Baguio, 2020)
This story is inspired by the Ga'dang weavers and beaders of Paracelis, Mt. Province. The Ga'dang group are found in Mountain Province, Isabela and Cagayan. They have distinct patterns found on their weaving, embellished with embroidery and beadwork.